Flexible super capacitor electrode and preparation method thereof - LIU ZHAOPING; ZHOU XUFENG; LIU YUEWEN (2017)
The invention provides a flexible super capacitor electrode which includes graphene paper and three-dimensional porous graphene compounded on the graphene paper. The graphene paper and the three-dimensional porous graphene are closely compounded to prepare a flexible super capacitor electrode. The graphene paper is mainly used for serving as an electrode current collector and giving the electrode good mechanical property. The three-dimensional porous graphene, which has a pore structure, a large specific surface area and good ion diffusion and charge storage abilities, gives the electrode excellent capacitance characteristic. By combining the advantages of the two different graphene structures in electrode mechanical property and energy storage, a high-performance flexible electrode with good mechanical property is obtained. 本发明提供了种柔性超级电容器电极，包括石墨烯纸以及复合于所述石墨烯纸的三维多孔石墨烯。本发明将石墨烯纸与三维多孔石墨烯进行紧密的复合制备柔性超级电容器电极，其中，前者主要承担电极集流体的作用，同时赋予电极良好的力学性能，后者具有孔结构且比表面积大，良好的离子扩散能力和电荷存储能力，赋予电极优异的电容特性，通过结合两种不同石墨烯结构在电极力学性能和能量存储上的优势，获得具有